Textiles asociados a la “niña sacerdotisa” de Cahuachi - Nasca - Bastiand Atto, María Soledad (2017)
This article extends the research study of the archaeological textiles recovered at an exceptional Nasca culture funerary bundle. Chronologically dated to the Early intermediate period (500 B. C. – 700 A. C.) from the archaeological monument” Cahuachi”, located southeast from the nowadays city of Nasca in Ica. The present funerary bundle was recovered during the archaeological excavations in 2009 by project Nasca - 2009, leaded by Dr. Giuseppe Orefici within the agreement Peru-Italy. This time I introduce the results of textiles, which constitute the funerary of the girl known as “the priestess girl” as they represent a meaningful qualitative sample.